Varietal and soil influence on nutritional status of sugarcane (Saccharum spp) as determined by foliar analysis - Haag, Henrique Paulo; Orlando Filho, José (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
Trials were established on four soil types (Latosolic B Terra Roxa - LR; Ortho Dark Red Latosol - LE and Red Yellow Podzolic Laras variation - PVls in the state of São Paulo and Textural B Terra Roxa - TE in Parana to study varietal and soil effects on macronutrient composition of sugarcane leaves and to do a nutritional survey of varieties by foliar analysis. A randomized block designwas used with four replications of 16 varieties (CB 41-76; CB 45-155; CB 47-355; CB 49-260; CB 56-171; CB 61-80; IAC 50/134; IAC 51/205; IAC 52/150; IAC 52/326; Co 740; Co 775; CP 51-22 and NA 56-62). Varieties were planted under the same conditions of climate, fertilization, tillage and age, sanitation and source. A central 20 cm portion of each +3 leaf was taken (except for midrib for determining amounts of N, R, K, Ca, Mg and S, expressed -on a dry weight basis. Leaf samplesof 20 leaves per plot were selected at four months of age, for analysis. From the results obtained it was conclued that: a) There is a varietal effect on leaf composition of major elements, independent of soil type; b) Soil type has an influence on leaf composition of different varieties; c) The higher nutrient levels in the leaves did not always result in the highest production intpol/ha; d) Because of soil and varietal influence on leaf composition it is rifficult to generalize critical nutrient, levels obtained from foliar diagnosis; e) Critical levels of nutrients obtained from foliar diagnosis for une variety do not represented the same levels for all varieties.